2022
DOI: 10.1155/2022/7652408
|View full text |Cite
|
Sign up to set email alerts
|

10-Year Weight Gain in 13,802 US Adults: The Role of Age, Sex, and Race

Abstract: Purpose. The primary objective of the present investigation was to identify 10-year weight gain patterns in 13,802 US adults and also to determine the extent that differences in 10-year weight gains were associated with the key demographic variables: age, sex, and race. Methods. The study design was cross-sectional and included the years 2011–2018. Data for 2019–2020 were not available because of COVID. A multistage random sampling strategy was employed. Specifically, individual sample weights and randomly sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 38 publications
0
11
1
Order By: Relevance
“…Consistent with prior studies, we found women who had an underweight or normal BMI at diagnosis had the greatest weight gain post-diagnosis 37 , 38 . The magnitude of weight gain we observed among certain subgroups in our cohort exceeds that of average adult females in the United States (0.54 kg/year) 39 . These findings highlight subgroups of breast cancer patients who are most at risk for large post-diagnosis weight gain and, in turn, support increasing awareness and monitoring of post-diagnosis weight change for these populations.…”
Section: Discussioncontrasting
confidence: 47%
“…Consistent with prior studies, we found women who had an underweight or normal BMI at diagnosis had the greatest weight gain post-diagnosis 37 , 38 . The magnitude of weight gain we observed among certain subgroups in our cohort exceeds that of average adult females in the United States (0.54 kg/year) 39 . These findings highlight subgroups of breast cancer patients who are most at risk for large post-diagnosis weight gain and, in turn, support increasing awareness and monitoring of post-diagnosis weight change for these populations.…”
Section: Discussioncontrasting
confidence: 47%
“…The prevalence of obesity is increasing nationwide with few successful long-term interventions. 1 Self-monitoring and coaching are successful strategies for managing obesity, but they require significant time commitment from coaches. 2 , 3 Primary care is an important source of weight management care and support given the large number of individuals who visit primary care clinics.…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of obesity has increased throughout the world over the last 50 years. According to the World Health Organization (WHO), its incidence has tripled since 1975 1 . Obesity results in low‐grade systemic chronic inflammation marked by increased circulating pro‐inflammatory cytokines (TNF‐α, IL‐1, IL‐6, and type‐1 interferons or IFNs) and different pro‐inflammatory immune cells (macrophages, mast cells, neutrophils, innate lymphoid cells [ILCs], and Th1 helper cells).…”
Section: Introductionmentioning
confidence: 99%